A STUDY ON COHESION IN THREE ARTICLES OF ALWASILAH - Agustini, Dila (2009)
his study is an analysis of cohesion in published texts written by Alwasilah. The texts are taken from his anthology "Language, Culture, and Education: A Portrait of Contemporary Indonesia" (2007). The analysis aims to see the writer's consistency in the use of cohesive devices throughout his works. This study employed mainly a qualitative method and involved three texts of Alwasilah that were randomly chosen. Halliday and Hasan' theory of cohesion (1976) and Eggins' analytical strategies are used to reveal the cohesive devices that occur in the texts. There are four principles of cohesion that are analyzed in this study; they are reference, lexical relation, ellipsis or substitution, and conjunction. This study exposes three main findings. First, cohesive devices that were employed within paragraphs are reference, lexical relation, conjunction, and ellipsis. There is no employment of substitution in the texts. Reference is the most prevalent device in all of the texts, with 683 occurrences (63%). This indicates that the writer tries to keep track of participants of the texts in facilitating the reading (Hoover 1997 as cited on Essem Educational Limited 2007). Second, cohesive devices that were employed inter-paragraphs are reference, lexical relation, conjunction, and ellipsis. There is no employment of substitution in the texts. Lexical relation is the most prevalent device inter-paragraphs, with 300 occurrences (60%). This indicates that the writer tries to keep track of topics of the texts for making texts hang together experientially (Halliday and Hasan 1976:288). Third, mostly, these texts cohesively have a clear focus, with only a couple major participants' chains developed in each text (Eggins 1994:321), except Text #3 with four major participants. With regard to the texture of the analyzed texts (Halliday and Hasan 1976:297), Alwasilah appears to have a periodic rhythm in writing his articles, which extends a dense cluster of cohesive ties within the paragraphs and leaves the texture inter-paragraphs relatively loose. Finally, among the three texts, Text #1 is the most cohesive texts, "Resurrecting Literature in Schools", where 94% of the devices are anaphorically interpreted, and only 6% are exophorically interpreted. Thus, it is more intelligible to the readers than the other texts. The second place is Text #3, where 88% of the devices are anaphorically interpreted, and 12% are exophorically interpreted. The last is Text #2 "Lament for Minor Languages", where 84% of the devices are anaphorically interpreted, and 16% are exophorically interpreted. Based on the main findings above, it can be concluded that all the articles of Alwasilah that were analyzed are cohesive where most cohesive ties in the texts are identifiable, except for the substitution. Without the ties, sentences or utterances would seem to lack any type of relationship to each other and might not be considered a text (Halliday and Hasan 1976:4). Therefore, much of the relevant information the readers might need is contained within the texts and thus, they are relatively easy to read.